Pengaruh Harga, Promosi Dan Kualitas Produk Terhadap Keputusan Pembelian Tanaman Hias Jenis Aglonema Dimasa Pandemi Covid 19 - Muhammad Abby Zama Daud (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
The purpose of this study was to find out about the effect of price, promotion, and purchasing decisions of Aglonema ornamental plants. A total of 40 respondents were used as research samples. Non-probability sampling with purposive sampling technique was the sampling technique used. Questionnaires were used as a data collection tool using validity tests and reliability tests. In this study used for data analysis. then the classic assumption test used is the multicollinearity test, the normality test and the heteroscedasticity test. Using the t-test, F-test, and the Coefficient of Determination (R2)) to assess the hypothesis in this study. The results of the F test value show that Price (X1), Promotion (X2), and Product Quality (X3), together have a significant influence on Purchasing Decisions (Y). The results of the t-test show that: 1. Price, 2. Promotion, 3. Product Quality, 4. Purchase Decision.